Would devils be devils with theoretical reason alone under a Kantian account? - Marcon Bark, Gehad (Studia Kantiana, 2025)
This paper focuses on Kant’s Towards Perpetual Peace famous statement according to which the problem of the State can be solved even for a race of devils, at least if they possess understanding. Its aim is to show that, despite Kant’s phrasing, understood as possessing the power of understanding alone, a devil would not be evil, nor accountable for his acts. A substantive account of this devil’s rationality can and shall be developed on the basis of Kant’s approach to practical agency in general. In this sense, understood as a rational being capable of end-setting under practical laws, a devil would have to be taken as an egotistical being who systematically acts out of self-interest. Under this presupposition, and at least from a juridical point of view in Kant, the hypothesis of a nation of devils offers a more interesting case for analysis.